Phenolic profiles of Portuguese olive fruits (Olea europaea L.): influences of cultivar and geographical origin - Vinha, Ana F. (2005)
The phenolic compounds present in 29 samples of olive fruits were analysed by reversed-phase HPLC/DAD and/or HPLC-DAD/ ESI-MS/MS. All samples were collected during the normal picking period for olive oil production, in north and central Portugal, and were obtained from 18 different olive cultivars. Two different extraction methods were necessary for the complete quantification of phenolic compounds, a methanolic extraction and an extraction which included a solid-phase extraction (SPE) cleaning step. The analyses showed that all samples presented a similar profile, which included at least six identified phenolic compounds: hydroxytyrosol, luteolin 7-O-glucoside, oleuropein, rutin, apigenin 7-O-glucoside and luteolin. Several samples also contained 5-Ocaffeoylquinic acid, verbascoside, quercetin 3-O-rhamnoside, cyanidin 3-O-glucoside and cyanidin 3-O-rutinoside. In all samples, hydroxytyrosol and oleuropein were the major compounds identified while, in general, rutin and luteolin 7-Oglucoside were the two main flavonoids. The influences of maturation index, nature of the cultivar and geographical origin are discussed.